Can poor states afford the fiscal responsibility legislation? - Sethi, Tanya (2009)
An analysis of revenue and expenditure trends in the six least developed states for the period 2003--04 to 2007-08 reveals how these states have met the Twelfth Finance Commission revenue deficit targets ahead of the 2008-09 deadline. In their rush to meet these targets, the states may have cut down expenditure in the very sectors where progress is most crucial to lift them out of their present least developed status. - Reproduced.
Keywords: Public finance